A Comparison of Empirically Based and Structured Professional Judgment Estimation of Risk Using the Structured Assessment of Violence Risk in Youth. (January 2014) - Childs, Kristina; Frick, Paul J.; Ryals, John S.; Lingonblad, Annika; Villio, Matthew J.
This study builds on a long-standing debate focusing on whether structured professional judgment (SPJ) or empirically based methods of risk estimation are more valid and reliable measures of future behavior by comparing three different measures of risk. Data were collected from the Structured Assessment of Violence Risk in Youth administered to a sample of 177 adjudicated juvenile offenders prior to being placed on probation. Three measures of risk were examined: an empirically derived measure of risk using latent class analysis, a violence risk based on SPJ, and a nonviolent delinquency risk based on SPJ. The ability of each measure to predict probation-related outcomes and recidivism was also addressed. Results provide moderate support for the continued use of the SPJ framework and highlight the need for future research regarding risk assessment procedures in juvenile justice settings.